BUILDING WORK COMMITMENT OF BPPT EMPLOYEE - Sugiarti, Endang (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2018)
The research result, obtained the findings as follows: The Leadership and competence both partially and simultaneously had positive and significant impact on work motivation with contribution (R2) 51%. Partially leadership dominantly influence on work motivation. Further on Structural 2 showed, The leadership, competence and work motivation both partially and simultaneously had positive and significant impact on employee’s performance with contribution (R2) 78%. Viewed as partial, competence had dominantly toward employee’s commitment. Concerning on direct and indirect effect, work motivation was being partial mediating. This study found and recommended that to increase employee’s commitment of technology agency research and application needed to be extending work motivation, reflected by the dimensions of affiliation which supported with an increase in competence which reflected by the dimensions of attitude, and rectified the leadership which reflected by the dimensions of supporting